Genomic imprinting and assisted reproduction - Paoloni-Giacobino, Ariane (BioMed Central, 2004)
Imprinted genes exhibit a parent-of-origin specific pattern of expression. Such genes have been shown to be targets of molecular defects in particular genetic syndromes such as Beckwith-Wiedemann and Angelman syndromes. Recent reports have raised concern about the possibility that assisted reproduction techniques, such as in vitro fertilization or intracytoplasmic sperm injection, might cause genomic imprinting disorders. The number of reported cases of those disorders is still too small to draw firm conclusions and the safety of these widely used assisted reproduction techniques needs to be further evaluated.